Gambaran Ansietas Lansia Dalam Mengadapi Proses Menjelang Ajal - Aprida Manurung (Lembaga Pengembangan Kinerja Dosen, 2023)
Elderly is someone who is over 60 years old. Older people will experience physical, psychological and cognitive decline, this can trigger anxiety / anxiety. Elderly who have entered old age often tell about their death, where the elderly begin to think about how much time is left in their life. it will cause aging to become depressed to affect its activities. This study aims to look at the description of anxiety in the elderly when approaching the process of dying. This study uses a quantitative method using the frequency distribution of each variable. This study found several findings including, of the 34 respondents the majority of the elderly had a moderate level of anxiety as much as 67.6%, the majority of elderly aged 60 to 74 years as much as 70.6%. the majority of the elderly are female as much as 52%, the majority have divorced marital status as much as 73.5%, and 52.9% of the elderly have elementary school education (SD). This finding can be interpreted that the level of anxiety/anxiety has a close relationship with the age of the elderly, gender, marital status and education of the elderly.